Capital Structure of Commercial Banks: A Comparative Analysis of NIBL, NABIL, HBL, EBL and SBI - Khanal, Mohan (Kathford Journal of Engineering and Management, 2023)
Capital structure is the combination of long term sources of funding i.e. preferred stock, common stock and long – term debt. Those are used to finance the firm. Capital structure analysis is the basis for analyzing the usefulness of accumulation from different sources of capital composition of capital is another factor, which affects the profitability. Loan capital dominant enterprises have less chance for prosperity despite of their huge profits.Capital structure decision is an important financial effect of capital on profitability and value of the firm. The present study will try to analyze and examine the capital structure of the commercial banks in Nepal. This article compares the capital structure of NIBL, NABIL, HBL, EBL and SBI five commercial banks which are currently operated as ‘A’ class banks in Nepal. It evaluates the capital structure and concludes that the total debt ratio of entire five banks is fluctuating. In order to compare the variables financial analysis, leverage analysis and correlation have been used as analytical tools. The conclusion is drawn on the basis of the total proportion of debt and equity capital of the institutions dealing with the problems in terms of capital formation and their overall effects and difficulties in its implementation.